BRIDGING THE DIGITAL GAP: TECHNOLOGY FAMILIARITY AS A PREDICTOR OF MOODLE USABILITY FOR EFL STUDENTS IN ALGERIA - Si-Mohammed , Bouchra; Bahloul, Amel (Armenian Folia Anglistika, 2025)
This comprehensive mixed-methods study investigates the role of technology familiarity in shaping the perceived ease of use of the Moodle platform among 91 first-year English as a Foreign Language (EFL) students and five instructors at the University of Batna-2, Algeria, during the 2023–2024 academic year. Quantitative surveys measured technology confidence, Moodle usability, and interaction behaviors, while qualitative responses provided contextual richness. Results revealed a moderate positive correlation between technology confidence and ease of use (r = .41, p < .001), with technology confidence explaining 16% of usability variance beyond demographic factors. Despite widespread smartphone ownership (97.8%), limited prior LMS experience (18.7%) and inconsistent internet access posed significant barriers. Students valued Moodle’s interactivity for the Civilization of the Target Language (CTL) course but found its text-heavy content unengaging. Instructors reported mixed perceptions, highlighting training deficits. Qualitative themes included accessibility benefits, engagement challenges, navigation difficulties, infrastructure barriers, training needs, and socio-cultural influences. Findings suggest that targeted interventions to enhance technology familiarity could optimize Moodle adoption in Algerian higher education, offering implications for e-learning equity in developing contexts globally.